2021
DOI: 10.1042/bsr20201707
|View full text |Cite
|
Sign up to set email alerts
|

A 12-week aerobic exercise intervention results in improved metabolic function and lower adipose tissue and ectopic fat in high-fat diet fed rats

Abstract: Investigations of long-term exercise interventions in humans to reverse obesity is expensive and is hampered by poor compliance and confounders. In the present study, we investigated intrahepatic and muscle fat, visceral and subcutaneous fat pads, plasma metabolic profile and skeletal muscle inflammatory markers in response to 12-week aerobic exercise in an obese rodent model. Six-week-old male Wistar rats (n=20) were randomized to chow-fed control (Control, n=5), sedentary high-fat diet (HFD, n=5), chow-fed e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 56 publications
0
10
0
1
Order By: Relevance
“…Skeletal muscle insulin resistance is a hallmark of obesity and type 2 diabetes mellitus [27]. Aerobic exercise reduces inflammation and improves insulin resistance in many tissues, including skeletal muscle [28]. In this study, we demonstrated that 8 weeks of aerobic exercise mitigated HFD-induced weight gain, insulin resistance, and chronic inflammation in the skeletal muscle of mice.…”
Section: Discussionmentioning
confidence: 53%
“…Skeletal muscle insulin resistance is a hallmark of obesity and type 2 diabetes mellitus [27]. Aerobic exercise reduces inflammation and improves insulin resistance in many tissues, including skeletal muscle [28]. In this study, we demonstrated that 8 weeks of aerobic exercise mitigated HFD-induced weight gain, insulin resistance, and chronic inflammation in the skeletal muscle of mice.…”
Section: Discussionmentioning
confidence: 53%
“…In obese adolescents, serum IGF-1 concentration is reduced, 4 weeks of moderate exercise can increase the activity but not the concentration of IGF-1 (Yang et al, 2018). Although IL-6 mRNA expression in skeletal muscle of high-fat diet rats is higher than that in the control mice, it could be reduced to a much lower level with aerobic exercise (Gopalan et al, 2021;Shirvani et al, 2021). While for diabetic patients, 6 months of resistance training had no effect on serum IL-6 concentration under the same weight loss condition (Miller et al, 2017).…”
Section: The Mechanism Underlying Exerciseinduced Expression Of Myokinesmentioning
confidence: 99%
“…Our histopathological findings indicate that high-fat nutrition and sedentary lifestyle may cause fat droplet accumulation within the skeletal muscle as expected. Moreover, GC/S muscle weight gain of high calorie fed sedentary rats was found to be related with an increase in adipose tissue mass together with intramyocellular lipid droplet accumulation (Gopalan et al 2021). However, aerobic exercise reduces fat droplet content in the skeletal muscle without significant differences in CPT-I and II mRNA expression levels.…”
Section: Skeletal Musclementioning
confidence: 99%